Biomechanical system elements: axial rotation profiling model with preset angular orientation parameters - Zagrevskiy, V. I.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2017)
The article considers a mathematical apparatus for computer modelling of pronator/ supinator muscle movements in a human body and demonstrates how the axial rotation of a biomechanical system element may be formally described using a set of matrix operations to profile rotation of a movable coordinate system around its own axes. Objective of the study was to develop a technological framework for the mathematical provisions and software to visualize the biomechanical system`s 3D position and orientation by the relevant computer tools. We have developed a computer software to visualize the 3D position and axial rotation of the model rectangular prism with the preset angular orientation parameters. The software was designed using Visual Basic 2010 Express algorithmic language in Visual Studio 2013 interactive design environment. It is the matrix description method to describe the 3D positions of the moving object plus the matrix multiplication method for presetting the necessary orientation and rotation that were applied to form a mathematical core of the software. The study shows that the human limb rotation and pronation may be modelled by a certain sequence of matrix multiplication operations i.e. by the elementary rotation matrixes being multiplied.